USE OF INFORMATION TECHNOLOGIES IN EDUCATION - Rashidovna, Muradova Firuza; Rashidovna Murоdova Zarina (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the article is to disclose the problem of using information technology in general education organizations. Based on the analysis of the regulatory framework, scientific and methodological literature on the research topic, the specifics of the implementation of information technologies in the study of individual subjects was determined. Particular attention is paid to the impact of computerization on the quality of education, examples of the use of information technology in education are disclosed. The article describes three main components of information technology as a complex of hardware, software and organizational and methodological support; The description of analog and digital information technologies is presented. The authors list the most common multifunctional office applications and IT tools; The advantages of using IT in the educational process are highlighted. The authors come to the conclusion that the use of information technology in education allows us to diversify a wide palette of forms and teaching methods, which are one of the modern ways of improving the educational process. The article is intended for teachers, methodologists, students, whose field of activity is associated with the development and use of modern information technologies in education.